2021
DOI: 10.1111/eci.13605
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0021087 acts as a miR‐184 sponge and represses gastric cancer progression by adsorbing miR‐184 and elevating FOSB expression

Abstract: Background Gastric cancer (GC) ranks third among the causes of cancer‐related deaths in the world. Circular RNA hsa_circ_0021087 (circ_0021087) plays a repressive role in GC. Nevertheless, the mechanism by which circ_0021087 constrains GC advancement is unclear. Materials and Methods Expression patterns of circ_0021087, microRNA (miR)‐184 and FBJ murine osteosarcoma viral oncogene homolog B (FOSB) mRNA were assessed by quantitative real‐time polymerase chain reaction (RT‐qPCR). Gain‐of‐function experiments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(74 reference statements)
1
7
0
Order By: Relevance
“…The biological role of circLMO1 in gastric cancer has been studied in previous studies ( 26 , 27 ). However, the mechanism by which circLMO1 regulates cancer progression remains poorly understood.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The biological role of circLMO1 in gastric cancer has been studied in previous studies ( 26 , 27 ). However, the mechanism by which circLMO1 regulates cancer progression remains poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al. showed that circLMO1 inhibits gastric cancer cell proliferation and invasion ( 27 ). In contrast, Han et al demonstrated that circLMO1 promotes gastric cancer cell proliferation ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peng et al demonstrated that circCUL2 modulates GC malignant transformation through miR-142-3p/ROCK2-mediated autophagy activation ( Peng L. et al, 2020 ). Recently, Yu et al revealed that highly expressed circ_0021087 induces GC cell apoptosis via the miR-184/FOSB axis ( Yu et al, 2021 ).…”
Section: Biological Functions Of Ncrnas In Regulating the Hallmarks Of Gastric Cancermentioning
confidence: 99%